Asymmetric synthesis of biaryl atropisomers by dynamic resolution on condensation of biaryl aldehydes with (−)-ephedrine or a proline-derived diamine - Ann Bracegirdle; Jonathan Clayden; Lai Wah Lai (Beilstein Journal of Organic Chemistry, 2008)
Atropisomeric biaryl aldehydes undergo diastereoselective condensation with (−)-ephedrine and with a proline-derived diamine, with selectivity highly dependent on solvent, temperature and reaction conditions. Levels of thermodynamic control up to 5:1 may be obtained by heating the diamine with the aldehyde in a sealed tube. Alternatively, crystallisation-induced dynamic transformation allows isolation of a single diastereoisomer in up to 85% yield. Hydrolysis and reduction of the major diastereoisomeric product of the reaction yields atropisomeric biaryls in >99:1 enantiomeric ratios.